Novel approaches for long-term lung transplant survival - Miller, Cynthia L.; O, Jane M.; Allan, James S.; Madsen, Joren C. (Frontiers in Immunology, 2022)
Allograft failure remains a major barrier in the field of lung transplantation and results primarily from acute and chronic rejection. To date, standard-of-care immunosuppressive regimens have proven unsuccessful in achieving acceptable long-term graft and patient survival. Recent insights into the unique immunologic properties of lung allografts provide an opportunity to develop more effective immunosuppressive strategies. Here we describe advances in our understanding of the mechanisms driving lung allograft rejection and highlight recent progress in the development of novel, lung-specific strategies aimed at promoting long-term allograft survival, including tolerance.